Combination immune checkpoint and targeted protein kinase inhibitors for the treatment of renal cell carcinomas - Robert Roskoski, Jr. (Pharmacological Research, 2024)
Kidney cancers comprise about 3% of all new malignancies in the United States. Renal cell carcinomas (RCCs) are the most common type of renal malignancy making up about 85% of kidney cancer cases. Signs and symptoms of renal cell carcinomas can result from local tumor growth, paraneoplastic syndromes, or distant metastases. The classic triad of presentation with flank pain, hematuria, and a palpable abdominal mass occurs in fewer than 10% of patients. Most diagnoses result from incidental imaging findings (ultrasonography or abdominal CT imaging) performed for another reason. Localized disease is treated by partial nephrectomy, total nephrectomy, or ablation (tumor destruction with heat or cold). When the tumors have metastasized, systemic therapy with protein-tyrosine kinase antagonists including sorafenib, sunitinib, pazopanib, and tivozanib that target vascular endothelial, platelet-derived, fibroblast, hepatocyte, and stem cell factor growth factor receptors (VEGFR, PDGFR, FGFR, MET, and Kit) were prescribed after 2005. The monoclonal antibody immune checkpoint inhibitor nivolumab (targeting programed cell death protein 1, PD1) was approved for the treatment of RCCs in 2015. It is usually used now in combination with ipilimumab (targeting CTLA-4) or cabozantinib (a multikinase blocker). Other combination therapies include pembrolizumab (targeting PD1) and axitinib (a VEGFR and PDGFR blocker) or lenvatinib (a multikinase inhibitor). Since the KEYNOTE-426 clinical trial, the use of immune checkpoint inhibitors in combination with protein-tyrosine kinase inhibitors is now the standard of care for most patients with metastatic renal cell carcinomas and monotherapies are used only in those individuals who cannot receive or tolerate immune checkpoint inhibitors.